Analgesic efficacy and opioid sparing effect of erector spinae planeblock in oncologic breast surgery: An observational study - ORHON ERGÜN, MELİHA; UMUROĞLU, TÜMAY; ZENGİN, SENİYYE ÜLGEN; UĞURLU, MUSTAFA ÜMİT (My University, 2022)
Background/Aim: Erector spinae plane block (ESPB) is a fascial plane block technique suitable for perioperative analgesia. This study aimed to evaluate the value of ESPB performed under ultrasound guidance and with ANI (Analgesia Nociception Index) monitoring in terms of intraoperative opioid need and postoperative pain management, in patients undergoing oncological breast surgery. Methods: This prospective case-control study includes forty-two female breast cancer patients who underwent unilateral modified radical mastectomy with axillary lymph node dissection. Patients were allocated to receive (ESPB group) or not receive (controls) ultrasound guided ESPB before anesthesia induction based on patient preference, and the groups were compared in terms of total intraoperative opioid consumption (with the guidance of ANI) and postoperative pain. Visual analogue scores (VAS) were obtained during the 12-hour postoperative follow-up. Results: Total intraoperative remifentanil dose required was significantly lower in the ESPB group when compared to controls (361.9 (108.3) vs. 1560.0 (4), P<0.001). ESPB group had significantly lower visual analogue scores at all postoperative time points. None of the patients in the ESPB group but all controls required additional analgesia during the 12-hour postoperative follow-up period. Conclusion: Ultrasound guided ESPB together with ANI monitoring is an effective and relatively safe perioperative analgesia method in patients undergoing mastectomy. Together, they provide an effective postoperative analgesia and reduce intraoperative opioid use consumption. Further studies will shed more light on the role of ESPB in this setting.
Keywords: Erector spinae plane block (ESPB); Oncological breast surgery; Perioperative pain; Opioid